Penggubalan Kurikulum Baru Sekolah Menengah: Jld. 7, 1985 Peranan Buku Teks Dan Peperiksaan Dalam Kbsm 1 - Ahmad, Hussein (Penerbit Universiti Sains Malaysia, 1985)
This paper attempts to discuss the function and relationships of two significant elements, text books and measurement of educational performance, within the conceptual framework of the proposed revision of the secondary school curriculum of the Malaysian education system. The paper argues that in the context of a centralised education system, text books and educational measurement appear to have far reaching implications especially with regard to the designing of the proposed revision of the curriculum as well as the efforts of inculcating desirable values among Malaysian youths. Thus, the function and status of both elements must be seen within the conceptual framework of the overall curriculum along with the other principal elements of the curriculum structure. It is envisaged that the thrust of the proposed revision of the curriculum is based on the concept of broad-based general education, as recommended by the Cabinet Report (1979) on education. Hence the two elements of textbooks and educational measurement should not precede the planning process of the proposed revision because these elements are consequential to rather than determinants of the final curriculum structure and its implementation process.